A resource-based approach to the valuation of African startups by venture capitalists - Odidambo, Blair Obanda (My University, 2021)
The valuation of a new firm is instrumental in entrepreneur financing. This research aims to create a consistent theoretical structure that seeks to determine whether variables identified as basic to a firm's performance in strategy theories explain the valuation of startups by venture capitalists. The main proposition of this research is that venture capitalists assess the variables that are essential to companies ' efficiency in valuing fresh companies. The specific pointer that venture capitalists look into is the qualities of the founder. This pointer will influence startups' valuation by venture capitalists when entrepreneurs seek financing from venture capitalists at the early development stages. The empirical findings of this study would also seek to develop an initial theoretical linkage between under-researched literature on venture capital maintenance and well-developed theories in strategic management. A theoretical rigor is added to the literature on investments by venture capitalists with the introduction ofthis approach.
Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Business Science in Actua1ial Science at Strathmore University